Supporting english instruction by implementing co-teaching and co-planning using the esp approach at the sena institution (2023)
Nowadays, the competition for jobs in Colombia is stricter than ever. Companies require their future employees to have not only extensive professional knowledge but also adequate English skills. The Servicio Nacional de Aprendizaje (SENA), an institution that has been training people in technical and technological programs, has responded to the demands of the productive sector by creating a bilingual program that aims to enhance students' competitiveness in the job market. This program targets A2 proficiency for technical programs and B1 proficiency for technologists. Although SENA has applied a bilingual project to assist its learners in achieving the necessary proficiency level, there are still various opportunities for enhancing the methodologies employed in English courses. Based on the aforementioned, the purpose of this project is to support the in-service teachers at SENA in the planning and teaching of English for specific purposes in the intermediate programs of the institution. Thus, co-planning, co-teaching, and the English for Specific Purposes approach were implemented through practices at SENA from the second semester of 2022 to the first semester of 2023 by three undergraduate students of the Bilingualism degree from a public university who assisted SENA learners from various intermediate programs to attain the required proficiency levels. Through the implementation of this project, SENA students enhanced their communicative skills in English for specific working fields, the SENA institution obtained additional support for the development of their bilingual program, and the pre-service teachers gained teaching experience and tools to improve areas such as planning, material design, and lesson organization.